Pengaruh vitamin C terhadap perkembangan gonad, daya tetas telur dan sintasan larva ikan lele dumbo (Clarias sp) - Sinjal, Hengky (Universitas Sam Ratulangi, 2014)
Abstract The purpose of this study was to investigate the effect of vitamin C with different doses of the long time ripe gonads, egg hatchability and larval survival of catfish (Clarias sp). This research used Complete Randomized Design (CRD) with four treatments each with three replications. The treatment in this study were different doses of vitamin C namely 0, 600, 1200 and 1800 mg / kg of feed. Data was analyzed usung analysis of variance and continued with the Smallest Real Difference test. Parent female catfish used was 1.5 years age with a weight of 800-900 g. Feed used was pellets supplemented with vitamin C. Fish was reared in four tanks measuring 2 x 1 x 1 m and fed every morning and evening ad libitum. The results of the study was the addition of vitamin C in the diet significantly influenced the speed of gonad maturation, egg hatchability and larval survival. Treatment with the addition of 1200 mg / kg of feed was the best treatment with gonadal maturation speed achieved on 39.33 days, the highest egg hatchability 83% and survival of larvae was 7.66 days. Keywords: Clarias gariepinus, Vitamin C, gonadal development, egg hatchability, larval survival.